An assessment of Raphitoma and allied genera (Neogastropoda: Raphitomidae). (1st November 2019) - Fassio, Giulia; Russini, Valeria; Pusateri, Francesco; Giannuzzi-Savelli, Riccardo; Høisæter, Tore; Puillandre, Nicolas; Modica, Maria Vittoria; Oliverio, Marco
ABSTRACT: The systematics of several Eastern Atlantic conoidean species, traditionally ascribed to the genus Raphitoma Bellardi, 1847, are revised on the basis of DNA sequence data from three gene regions (cytochrome c oxidase subunit I, 16S rRNA and 12S rRNA). We assign genus ranking to three major lineages ( Raphitoma, Cyrillia Kobelt, 1905 and Leufroyia Monterosato, 1884) and suggest that two West African species belong in the subgenus Daphnella ( Paradaphne ) Laseron, 1954. A new classification, based on molecular systematics and critical study of morphology, is provided for all Eastern Atlantic and Mediterranean species that are currently ascribed to Raphitoma s.l. The genus Clathromangelia Monterosato, 1884 is confirmed as belonging to Raphitomidae. Phylogenetic relationships and genetic distances suggest that Raphitoma maculosa Høisæter, 2016 and R. obesa Høisæter, 2016 may be divergent morphotypes of R. bicolor (Risso, 1826) and Cyrillia aequalis (Jeffreys, 1867), respectively.